Lets get active: learning about peoples and places - Chowdhary, Eman (New Delhi The Energy and Resource Institute, 2014)
Lets Get Active: Learning about Peoples and Places (An illustrated activity book that teaches young learners all about people and exciting places) Learning about People and Places educates young learners about famous places in the world and people belonging to different cultures. It explains interesting facts about our wonderful world through a lot of spot-the-difference, maze, dot-to-dot, and colouring activities, besides simple counting and writing exercises. Its easy-to-do activities promote creative thinking and problem solving among young minds, making the title a fun supplement to their textbooks, while acquainting them with various people and places of our planet.
Keywords: People and Places; Activity book